Enzymatic Hydrolysis And Lactic Acid Bacteria Fermentation Of Okara - Mahmud, Nur Adilla (Universiti Sains Malaysia, 2020)
The production of soybean products has been increasing throughout the world and there has been a corresponding increase in the quantity of soybean curd residue or okara being thrown out. The dumping of okara has become a problem to be solved due to its contamination to the environment. Okara is rich in fiber, fat, protein, vitamins and trace elements. Okara has potential for value-added processing and utilization which simultaneously hold the promise of increased economic benefit as well as decreased pollution potential for the environment. In this study, the optimum condition for enzymatic hydrolysis of okara on release of sugar was studied and the total protein content of okara after fermentation by lactic acid bacteria (LAB) was investigated.